Analisis Nilai-Nilai Karakter Nasionalisme dalam Novel Ayah Karya Andrea Hirata - Astarina, Wa Ode Fina; Supriadi, Supriadi; Erniati, Erniati (JURNAL EDUKASI NONFORMAL, 2024)
This research aims to provide an overview of the Nationalist Character Values ​​in the Novel Ayah by Andrea Hirata. The main problem in this research is how to describe the character values ​​of nationalism in Andrea Hirata's novel Ayah. Based on the research results, the nationalist character values ​​contained in the novel Ayah by Andrea Hirata consist of the following nationalist character values: Love of the Motherland, Love of Peace, Discipline, Hard Work, Demonstration, Respect for Other People's Achievements.